MONEY LAUNDERING AS ECONOMIC DIMENSION OF TERRORISM - Jelena Dinić (Zbornik Pravnog Fakulteta Sveučilišta u Rijeci, 2016)
This paper presentsan economic dimensionof terrorism through analysis of terrorist organizations needs for funding, modules of financing terrorism and links to money laundering. Financial resourcesare one of the most important conditions for maintaining infrastructure of terrorist organizations and carrying out terrorist activities. Assets acquired through legal and illegal channels members of the terrorist organization carry out through financial system by using techniques ofmoney laundering in order to conceal the trace of money needed for organizing terrorist attacks. Due to the global nature of the problem of money laundering and terrorist financing, preventive mechanisms include cooperation of financial intelligence agencies and international organizations as well as strengthening of national institutions that are dealing with this problem. Numerous recently adopted guidelines, conventions and recommendations (within the EU, OUN, FATF) draw attention for detection terrorist activities in the preparatory phase, such as travel of terrorists, financing logistical support for their activities and weapons (explosives) supply required for carrying out terrorist attacks.